Penerapan Arsip Elektronik dengan Rail Document System di PT D Jakarta - Rani Fitriani; Trisni Handayani (Jurnal Utilitas, 2019)
This research aims: to determine the application of electronic archives through the Rail Document System in PT D Jakarta. This research uses qualitative descriptive research methods. The data acquired from 3 informants sources selected purposive sampling with a shared interview 3 speakers who mastered and understood the electronic archives of 1 person, the Manager of the document UNIT, 1 Junior Manager of the document unit, and 1 employee of the document Unit. Data collection techniques in PT D Jakarta is done by participatory observation, in-depth interviews, and documentation. From the results of the research, the application of electronic archives through the Rail Document System at PT D Jakarta includes the creation and storage, use and distribution, maintenance, and depreciation. In creation and storage covers 3 aspects namely sorting, scanning, and electronic storage media. In use and distribution include electronic archive security system. In the maintenance covers software and hardware. And in the depreciation process is the process of transferring electronic archives. Keywords: Electronic Archives, Rail Document System, Archive Lifecycle